2018
DOI: 10.1080/13854046.2018.1503333
|View full text |Cite
|
Sign up to set email alerts
|

Visual-spatial processing style is associated with psychopathology in adolescents with critical congenital heart disease

Abstract: Objective: To determine whether visual-spatial processing style is associated with psychopathology in a large sample of adolescents with critical congenital heart disease (CHD). Local (part-oriented) style was hypothesized to increase risk for internalizing (but not externalizing) forms of psychopathology. Method: Participants included 278 adolescents with critical CHD (dextro-transposition of the great arteries = 134, tetralogy of Fallot = 58, single-ventricle cardiac anatomy requiring the Fontan procedure = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Additionally, the studies implied that adolescents with CHD, in particular adolescents with single-ventricle defects, were at increased risk of lifetime psychiatric diagnoses, attention-deficit/hyperactivity disorder, and selfreported anxiety. [101][102][103][104][105][106] Meta-analysis of IQ scores. The data of the papers addressing IQ outcomes at preschool age, school age, and adolescence using the Wechsler Preschool and Primary Scale of Intelligence or Wechsler Intelligence Scale for Children evaluations (full-scale IQ, verbal IQ, or performance IQ scores) were entered into the meta-analysis.…”
Section: Review 35mentioning
confidence: 99%
“…Additionally, the studies implied that adolescents with CHD, in particular adolescents with single-ventricle defects, were at increased risk of lifetime psychiatric diagnoses, attention-deficit/hyperactivity disorder, and selfreported anxiety. [101][102][103][104][105][106] Meta-analysis of IQ scores. The data of the papers addressing IQ outcomes at preschool age, school age, and adolescence using the Wechsler Preschool and Primary Scale of Intelligence or Wechsler Intelligence Scale for Children evaluations (full-scale IQ, verbal IQ, or performance IQ scores) were entered into the meta-analysis.…”
Section: Review 35mentioning
confidence: 99%
“…Preoperative [55][56][57][58][59][60][61][62] Hypertonia and hypotonia, motor asymmetries, abnormal suck and swallow Abnormalities in behavioral state organization Seizures, abnormal background EEG patterns Microcephaly White matter injury, low cerebral volume Postoperative 55,[63][64][65][66][67][68][69][70][71][72][73][74] Jitteriness Motor asymmetries Abnormal tone Seizures, abnormal EEG background activity New white matter injury, delayed cortical brain growth Infancy [75][76][77][78][79][80][81][82] Oral-motor dyscoordination Gross motor delays Abnormalities in behavioral state organization Impaired short memory Toddler 73,75,[83][84][85][86][87][88] Apraxia of speech Gross and fine motor delays Internalizing and externalizing behaviors Increased incidence of autism Hearing loss Cognitive delays School age child [89][90][91][92][93][94][95][...…”
Section: Time Framementioning
confidence: 99%
“…In our sample of adolescents with critical CHD, we found that individuals categorised by the Rey-Osterrieth Complex Figure as having a part-oriented processing style were indeed two to three times more likely to meet formal diagnostic criteria for an anxiety disorder, but were at no greater risk of having a mood disorder, disruptive behaviour disorder, or attention-deficit/hyperactivity disorder, relative to those with more holistic styles of processing. 83 It seems, therefore, that this particular style of linear, detail-focused processing may be uniquely associated with anxiety in adolescents with CHD, although further research is needed to understand whether part orientation in adolescence may also increase the risk for the development of depression later on.…”
Section: Flexibility and Processing Stylementioning
confidence: 99%
“…Acceptance and commitment therapy has also been described as a therapeutic modality that "excels at transforming the abstract into the concrete" 85, p.287 an attribute that may be especially important for children and adolescents with the most severe forms of critical CHD, whose part-oriented styles of processing may undermine perspective-taking and make it harder for them to manage abstraction and generalise coping strategies to situations outside the clinical setting. 83 Thus, it is recommended that acceptance and commitment therapy, mindfulness-based interventions, and Unstuck and On Target be examined in children and adolescents with CHD. Moreover, to address existing health disparities among individuals with CHD, it will be important to make use of intervention delivery modalities such as telehealth that are likely to increase access and reduce barriers to care.…”
Section: Section Summarymentioning
confidence: 99%